Development of entrepreneurial interest in business actors through communication strategies in Pangandaran - Hanny Hafiar; FX Ari Agung Prastowo; Dwi Masrina; Priyo Subekti (Jurnal Kajian Komunikasi, 2022)
The gap between job vacancies and job seekers has increased the number of unemployed in Indonesia. Even a fact shows an ironic phenomenon appearing in the world of Indonesian education that the higher a person's education, the higher the probability of becoming unemployed. One of the problems in Pangandaran is that the number of entrepreneurs is not ideal, so the ratio is at 2.5%, which means it is still below the national entrepreneurship ratio of 3.6%. The problem in increasing the number of entrepreneurs in Pangandaran is the mindset and readiness of the MSME actors themselves and capital. This study aims to determine how the development of entrepreneurial interest of small business actors through communication strategies in Pangandaran by the Pangandaran Regional Government, in this case, the Department of Trade, Cooperatives, and MSMEs. The method used is the descriptive method with qualitative and quantitative data. The study results show that the Cooperatives and MSME Office uses three methods of communication strategy: 1) education through counseling and socialization; 2) dissemination of information through social media and internet-based media; 3) dissemination of information through communication networks called the entrepreneurial community. The obstacles faced are: 1) capital factors; 2) mindset about entrepreneurship; 3) the low level of education which impacts the lack of adaptation in using ICT; 4) business actors do not fully understand the rules and policies related to MSMEs; 5) communication network is not optimal.